The Influence of The Use of The Square Quantum Learning Model on Poetry Writing Skills Students in Class VIII SMP Negeri 3 Kecamatan Payakumbuh - Hendrisman Hendrisman (Indonesian Language and Literature Education Study Program and LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2019)
This study aims to describe (1) poetry writing skills of eighth grade students of SMP Negeri 3 Payakumbuh District using conventional methods. (2) poetry writing skills of eighth grade students of SMP Negeri 3 Payakumbuh District using a type of quantum learning model. (3) the effect of using the quantum teaching model of quantum teaching to the poetry writing skills of eighth grade students of SMP Negeri 3, Payakumbuh District. This research is using experimental method. Data analysis shows that the quantum teaching model of quantum tandur is influential in learning to write poetry in Indonesian subjects in the experimental class. This is due to an increase in student grades which at the time of the pre-test mean value () is 67. After applying the type of quantum learning model (quantum teaching) in the learning process at post-test with an average value () is 80. This is seen from the results of the comparison of tcount with ttable (, 6798> 2,021) because tcount is greater than ttable then Ha (alternative hypothesis) is accepted. So, the learning outcomes of experimental class students who are taught with quantum teaching models are better than the learning outcomes of control class students who are taught using conventional methods. Abstrak Penelitian ini bertujuan untuk mendeskripsikan (1) keterampilan menulis puisi siswa kelas VIII SMP Negeri 3 Kecamatan Payakumbuh menggunakan metode konvensional. (2) keterampilan menulis puisi siswa kelas VIII SMP Negeri 3 Kecamatan Payakumbuh menggunakan model pembelajaran kuantum (quantum teaching) tipe tandur. (3) pengaruh penggunaan model pembelajaran kuantum (quantum teaching) tipe tandur terhadap keterampilan menulis puisi siswa kelas VIII SMP Negeri 3 Kecamatan Payakumbuh. Penelitian ini menggunakan metode eksperimen. Analisis data menunjukkan bahwa model pembelajaran kuantum (quantumteaching) tipe tandur berpengaruh dalam pembelajaran menulis puisi pada mata pelajaran bahasa Indonesia di kelas eksperimen. Hal ini dikarenakan adanya peningkatan nilai siswa yang mana pada waktu prates nilai rata-rata () adalah 67. Setelah diterapkan model pembelajaran kuantum(quantum teaching) tipe tandur dalam proses pembelajaran pada waktu pascates dengan nilai rata-rata () adalah 80. Hal ini di lihat dari hasil perbandingan thitung dengan ttabel ( ,6798>2.021) karena thitung lebih besar dari ttabel maka Ha (hipotesis alternatif) diterima. Jadi, hasil pembelajaran siswa kelas eksperimen yang diajar dengan model pembelajaran kuantum (quantum teaching) tipe tandur lebih baik dibanding hasil pembelajaran siswa kelas kontrol yang diajar menggunakan metode konvensional. Kata kunci: model pembelajaran, kuantum (quantumteaching), tipe tandur, keterampilan menulis puisi